(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article comprehensively analyzes the role of medical insurance in the health care system of Uzbekistan, the theoretical, institutional and socio-economic foundations of its implementation. In the course of work, the introduction of the compulsory medical insurance (MHI) system is considered as an important mechanism for achieving Universal Health Coverage (UHC). The actuarial and theoretical approaches developed by Pitacco are analyzed, adapted to the conditions of Uzbekistan, and the need for collective sharing of health-related financial risks is substantiated. The article highlights the importance of determining insurance premiums, the regulatory role of the state, the high share of the informal sector and solidarity financing in conditions of uneven income distribution.